THE USE OF THINK ALOUD STRATEGY TOWARD STUDENTS’ READING COMPREHENSION ON ENGLISH TEXT - Iin Widya Lesatri; Retno Dewi Utari Ningrum; Mohammad Fatoni (Jurnal Ilmiah Hospitality, 2020)
The objective of this research is to know the difference situation of students before and after giving treatment and to know the effect of using Think Aloud Strategy toward students’ reading comprehension on English text at second semester of the eighth grade of SMP N 2 WIDANG in the academic year of 2018/2019. It is consists of 7 classes, VIII A- VIII – G, using cluster random sampling. In this research, the population was the eighth grade of SMP N 2 WIDANG. In collecting the data, researcher used test as research instrument in the form of multiple choice, the test consist of 25 multiple choice item. From the data analysis computed by using SPSS. The result of the data indicated that, there was difference between the value of students pre-test and post-test. The mean score of post-test (76.13) was the higher than the score obtained in the pre-test (70,25). From t- count, the researcher found that, the value of t-count (2.152) was higher than t-table (1.671) at the level of significance 0.05 degree of freedom (df) = 62. Based on the finding of the research, the researcher concluded that Think Aloud Strategy (TAS) had effective toward students’ reading comprehension on English text.